Nyai Hj. Masriyah Amva: Corak kepimpinan wanita dari aspek perundangan Islam / Qisti Robhati - Qisti , Robhati (2018)
This research describes about a woman who leads Kebon Jambu Al-Islamy Islamic boarding school and about how she solves the verify challenges also about her struggle towards her surrounding environment that still reject the gender equality. The feature of women leadership is used by her as a leader to interact with her surrounding people to achieve boarding school’s goals. However, the different of the leadership style between men and women become the challenges that should be thought. Furthermore, the aim of this research is to understand: 1) The description of woman leadership in many perspectives. 2) The description of leadership’s characteristics of Nyai Hj. Masriyah in Islamic law perspective. 3) The description of Nyai Hj. Masriyah’s efforts on dealing with many challenges in her leadership. There are a lot of challenges faced by Nyai Masriyah throughout her carrier. Apart from that, she becomes the leader of that Islamic boarding school now is just because of her experiences that lead her there. This study is a qualitative study and case study on Life Story and various multiple cases that based on personal documents, interview which were conducted in person with some parties in Pesantren Kebon Jambu Al-Islamy, Cirebon, Indonesia and direct observation. The result of the research reveals that Nyai Hj. Masriyah implements the leader and managerial function in her leadership. Her leadership on Islamic boarding school and organization is not an issue because she has the capability of leadership and her leadership is based on Islamic sharia. It could be concluded also that Nyai Hj. Masriyah has the aspect and commitment on Islamic classic literature in religio-cultural construction and it becomes the clearly leadership characteristic in sustaining the culture of organization and Islamic boarding school, in order to build the character of the student and institution which differentiates with other Islamic vi boarding schools, and not to be fanatic of experience, because it may mislead the organization an Islamic boarding school. This research put Islamic law aspect to deal with the temporary cultural society.